Development of Learning Media Programmable Logic Control on Electric Motor Installation Courses in SMKN 2 City of Serang - Perdana, Gilang; Permata, Endi; Fatkhurrokhman, Mohammad (Universitas Lampung, 2021)
The focus of this research is to find out the process of making PLC learning media, measuring the feasibility level of PLC media, measuring the feasibility level of learning jobsheets, and measuring the effectiveness of learning media and jobsheets at SMKN 2 Serang City. The research method used in this study is Research and Development (R&D) with the ADDIE model developed by Robert Branch and reduced according to the needs of the researcher, which includes: (1) Analyze, (2) Design, (3) Develop, (4) Implement, (5) Evaluate.Tahap got problems not already own analysis of instructional media for subjects PLC Installation Motor Listrik.Tahap Design is a step for designing learning mediaPLC and jobsheet learningPLC.TahapDevelopment is a stage further learning media making media created rated by experts media andexperts worksheet. The implementation phase was carried out in class XI TL 1 SMKN 2 Serang City starting with a pretest to determine the extent of students' knowledge about PLC and then applying the learning media that had been developed. The last stage of evaluation is done by post test to determine the effectiveness of the media that has been made. Based on the results of the study, the results obtained: (1) PLC learning media and PLC learning worksheets were developed based on themethod Research and Development with the ADDIE development model, (2) The feasibility of the media based on the assessment of media experts got a score of 114